Affirmative Approach in Strengthening Women’s Access to the Information and Communication Technology’s Vocational Training - Muhamad, Tauvik; Wiryasti, Hirania; Novitasari, Eka (Yayasan Jurnal Perempuan, 2021)
Despite growing of internet users and digitalizing economy as result of Industry Revolution 4.0, Indonesia experiences with digital divide in which young women are still left behind in the digital economy. To address the issue, affirmative action in accessing skills development and labour market are crucial. The aim of the study is observing whether affirmative action for women exist and it helps to address the issue. The paper uses mixed qualitative and quantitative methods in which primary and secondary data collected respectively through interview, and online survey as well as literature review. The study argues that the affirmative action will not be adequate to address gender inequality in the digital economy, unless integrated approaches through capacity building and women engagement are in place. The paper concludes that the affirmative action is only effective if the intervention integrated with skills development and women engagement at various level of process for policy formulation and its implementation. Â